Anthropomorphic tendon-driven robotic hands can exceed human grasping capabilities following optimization. (April 2014) - Inouye, Joshua M.; Valero-Cuevas, Francisco J.
How functional versatility emerges in vertebrate limbs in spite of their anatomical complexity is a longstanding question. In particular, fingers are actuated by numerous muscles pulling on tendons following intricate paths. In contrast, the tendon-driven robotic hands with intuitive tendon routings preferred by roboticists for their ease of analysis and control do not perform at the level of their biological counterparts. Thus there is much debate on whether and how the anatomy of the human hand contributes to grasp capabilities. These parallel questions in biology and robotics arise partly because it is unclear how the number and routing of tendons offer functional benefits. We use a novel computational approach that analyzes tendon-driven systems and quantifies grasp quality to compare the precision grasp capabilities of thousands of robotic index finger and thumb designs vs. the capabilities measured in human hands. Our exhaustive search finds that neither the symmetrical designs sometimes preferred by roboticists nor randomly generated designs approach the grasp capabilities of the human hand (they are on average 73% weaker). However, optimizing for anatomically plausible asymmetry in joint centers, tendon routings, and maximal tendon tensions produces designs that can exceed the human hand by 13–45%, and outperform the preferred robotic designs by up to 435%. Thus, the grasp capabilities of prosthetic or anthropomorphic hands can be greatly improved by judiciously altering design parameters, at times in counter-intuitive ways. Moreover we conclude that, in addition to its other capabilities, the human hand's anatomy is very advantageous for precision grasp as it greatly outperforms numerous alternative robotic designs.